REGIONAL COOPERATION AND LEGAL PROTECTION TO INDONESIAN WOMEN MIGRANT WORKER - Djelantik, Sukawarsini (Indonesian Journal of International Law, 2016)
The increasing number of Indonesian women migrant workers (IWMWs) started since 1997, and remain high after the global financial crisis in 2008. The impact for Indonesian economy is quite significant in terms of social and economy. Unemployment rate increased significantly as well as number of people living below poverty line. Social and family relations changed as women forced to work in public sectors to support family economy. Domestic job scarcity turned thousands of Indonesian women as family bread winner by working overseas. The above push factors are combines by increasing demands of IWMWs in the newly industrialized countries in Southeast Asia, especially Singapore and Malaysia. Geographic and cultural proximity also become reasons both countries are favorite destination to IMWs. As IMWs are mostly uneducated, so they left with no or little choices rather than working as domestic servant or other low income jobs known as 4D’s jobs (dirty, dangerous, difficult, demeaning) under poor working conditions. These marginal conditions were the result of weak bargaining position especially compared to other nationality, such as the Filipinos. Marginality also led to the emergence of the issue related to the violation of human and worker rights. To solve the problems, ASEAN countries need to cooperate and to build a solid legal system to protect IWMWs. The conflicting interests within ASEAN member countries between the receiving (Singapore, Malaysia) and sending (Indonesia, The Philippines, Thailand) have prevented the regional organization to produce binding legal products to protect its migrant workers. This research will answer questions: “what are solutions to increase IWMWs bargaining position in regional work force?” Other question would be: “How ASEAN solve regional news related migration issue”.